2022
DOI: 10.3389/fendo.2022.1012416
|View full text |Cite
|
Sign up to set email alerts
|

Is oxidative stress evaluated in viable human spermatozoa a marker of good semen quality?

Abstract: BackgroundOxidative stress is defined as the unbalance between reactive oxygen species (ROS) production and antioxidant defences. Whereas low levels of ROS are necessary for physiological sperm functions, high levels impair fertility damaging membranes, proteins and DNA. In this study, we used two probes, CellROX® Orange and Dihydroethidium (DHE), which reveal different intracellular ROS species, to evaluate the association between the percentage of oxidized viable spermatozoa and sperm functions.MethodsThe pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…No increase was observed in viable spermatozoa with both probes. In a previous study, we demonstrated that CellROX ® Orange-and DHE-positive viable spermatozoa are associated with good semen characteristics and do not show apoptotic features, reflecting a sperm fraction related to better performances [34]. We hypothesized that most ROS-positive viable spermatozoa show physiological ROS levels [34] likely supporting their physiological functions [51,52].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…No increase was observed in viable spermatozoa with both probes. In a previous study, we demonstrated that CellROX ® Orange-and DHE-positive viable spermatozoa are associated with good semen characteristics and do not show apoptotic features, reflecting a sperm fraction related to better performances [34]. We hypothesized that most ROS-positive viable spermatozoa show physiological ROS levels [34] likely supporting their physiological functions [51,52].…”
Section: Discussionmentioning
confidence: 92%
“…An important aspect concerns the mechanism(s) responsible for BaP detrimental effects on spermatozoa. We investigated the possible role of induction of oxidative stress by evaluating intracellular ROS with two probes, CellROX ® Orange, which shows specificity for H 2 O 2 only in viable spermatozoa and DHE, which detects both H 2 O 2 and O 2 − species both in viable and unviable spermatozoa [34,50]. We found that all the three tested concentrations of BaP increased the percentage of ROS-positive unviable swim-up selected spermatozoa as detected with DHE after 3 h of incubation, likely reflecting the slight decrease in viability detected in the same sample (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are in agreement with data obtained by other authors, who have shown that subjects with higher sORP (> 1.34; > 1.36; > 1.47) had significantly lower sperm progressive motility [111][112][113] and higher SDF. 112 Moreover, it has been shown that ROS levels are adversely correlated with progressive motility 53,106,[111][112][113][114][115][116][117][118] and positively correlated with SDF. 53,106,112,114,116 The linear associations among sperm motility, SDF and sORP were also confirmed in our current and previous studies.…”
Section: F I G U R Ementioning
confidence: 99%
“…112 Moreover, it has been shown that ROS levels are adversely correlated with progressive motility 53,106,[111][112][113][114][115][116][117][118] and positively correlated with SDF. 53,106,112,114,116 The linear associations among sperm motility, SDF and sORP were also confirmed in our current and previous studies. 79,87 However, Garcia-Segura et al 119 showed that sORP negatively correlated with sperm progressive motility and positively correlated with a deficiency of sperm chromatin-specific proteins (protamines).…”
Section: F I G U R Ementioning
confidence: 99%